Manejo de alternativas biológicas para el control de Coptoborus ochromactonus en el cultivo de balsa (Zambrano M. 2017)” - López Meza, Wilmer Jhon (2022)
The “balsa” is currently an export product of great importance for the country, since Ecuador is one of the main exporters, mainly to Asia, Europe and North America as frequent destinations. There are approximately 20,000 hectares of raft plantations in the country that serve this purpose and for national use. Also, the Coptoborus ochromactonus is an insect pest, commonly called the moth of balsa, which has been destroying trees, with a 58% incidence and up to 25% of mortality in plantations. This study is a documentary review of secondary information in different academic search engines to determine the most appropriate biological alternatives for the management and control of Coptoborus ochromactonus and to promote its use and mitigate the damage caused by this pest. Several research shows that the highest rate of pest incidence and mortality occurs in the adult tree, which has reached 3 years, and also emphasizes the use of beauveria bassiana and metarhizium anisopliae for insect control. These alternatives have reached an effectiveness of 97.5% to the plague control, in two investigations, which recommend their use since they are highly effective as the chemical alternatives that are currently used